Genetic diversity of MHC and coccidial mitogenomes from fecal samples of the red‑crowned crane (Grus japonensis) - Wei Xu; Xinyi Zhao; Nan Xu; Ying Zhu; Keyi Tang; Ke He; Hongyi Liu (The Veterinary Journal, 2026)

A pyrrhotite-biochar composite enables short-HRT simultaneous nitrate and phosphate removal with suppressed sulfate and iron release - Fei Gao; Xin Xiong; Wenwen Xie; Jing Tian; Keyi Wei; Qingzhi Li; Yong Liu; Zhouliang Tan (Journal of Water Process Engineering, 2026)

Distance-aware cooperative Kriging-assisted evolutionary algorithm for expensive many-objective optimization - Junhua Liu; Keyi Kou; Wei Zhang; Meng Wang; Mengnan Tian (Swarm and Evolutionary Computation, 2026)

Lapatinib Induces Ferroptosis in Cardiomyocytes by Regulating ATF4/GPX4 - Yue Sun; Keyi Jiang; Dan Wang; Chunlei Li; Yuqing You; Long Chen; Wei Chang; Liwei Zhang; Hongqi Feng; Dandan Li; Yilan Li (Cardiovascular Toxicology, 2026)

A transcriptome dataset for early phenotypic sex differentiation in the mud crab Scylla paramamosain - Haolin Yang; Zhiqiang Liu; Chunyan Ma; Wei Wang; Lingbo Ma; Keyi Ma (Frontiers in Marine Science, 2026)

High-performance and recyclable HKUST-1-derived CuxO/Steel electrode for electrocatalytic dechlorination of trichloroacetic acid - Mengyuan Xu; Yunhua Lv; Keyi Xu; Liqin Zhong; Kunming Wei; Xiaoyan Ma; Su Jiang; Jing Deng; Hanxuan Zeng; Qingsong Li; Stefanos Giannakis; Andrea M. Dietrich (Journal of Cleaner Production, 2026)

Impact of emission inventory uncertainty on secondary inorganic aerosol simulation over Beijing–Tianjin–Hebei region - Yulong Li; Xiao Tang; Keyi Chen; Lei Kong; Wei Feng; Tianming Lu; Kai Cao; Quan Zhang; Zifa Wang (Atmospheric Pollution Research, 2026)

Comparative transcriptomic analysis of the megalopa metamorphosis development reveals candidate genes associated with developmental remodeling and putative brachyurization in the mud crab Scylla paramamosain - Keyi Ma; Likun Xu; Zhiqiang Liu; Xueyang Wang; Lingbo Ma; Chunyan Ma; Wei Wang (Frontiers in Marine Science, 2026)

Investigation of SNPs at NKCC Gene of Scylla paramamosain to Unveil the Low-Salinity Tolerance Phenotype - Chunyan Yin; Yanqing Ma; Zhiqiang Liu; Xueyang Wang; Keyi Ma; Wei Wang; Chunyan Ma; Fengying Zhang (Fishes, 2026)
The Na+/K+/2Cl− cotransporter (NKCC) gene encodes a critical membrane transporter involved in cellular ion homeostasis and plays a pivotal role in osmoregulation and salinity adaptation in aquatic organisms. This study identified and validated SNP markers in the NKCC gene associated with low-salinity tolerance in Scylla paramamosain. Four SNPs (g.196C>A, g.8374T>A, g.8385T>A and g.91143T>A) were screened and genotyped in low-salinity tolerant and intolerant groups. Association analysis revealed that mutant genotypes at all four sites were significantly enriched in the tolerant group (p

Deciphering spatio-seasonal impacts of agricultural irrigation on water quality evolution and surface water-groundwater interaction in a large irrigation district, northwest China - Muhan Li; Keyi Zhang; Wei Bao; Shen Qu; Guanglei Yu; Yansong Bai; Xu Yang; Zeyuan Liu; Hongli Ma; Ping Miao; Fuyang Huang; Ruihong Yu (Journal of Hydrology, 2026)

Covalency modulated by Fe-F-Fe configuration and oxygen vacancy promotes dual mechanism for oxygen evolution reaction - Bo Feng; Keyi Lv; Ziyong Zhang; Nianwen Song; Ziyang Yan; Yuchao Zhang; Yanfei Wei; Xiaofei Yu; Lanlan Li; Xinghua Zhang; Xiaojing Yang; Zunming Lu; et al. (Chemical Engineering Journal, 2025)

Shipowners’ responses to carbon tax: speed optimization using AIS data - Hailing Liu; Keyi Ju; Xiaozhuo Wei; Chenjun Zhang; Jianghang Zhou (Clean Technologies and Environmental Policy, 2025)

Environmental exposure to heavy metals and their potential impact on prostate cancer prognosis-related gene expression - Wei Song; Tao Zhang; Jianliang Ou; Jinliang Ni; Jiong Tang; Houliang Zhang; Haipeng Zhang; Guangchun Wang; Jun Chang; Bo Peng; Keyi Wang (Food and Chemical Toxicology, 2025)

Geochemical behaviors of metal elements during a single flood event in the natural Chishui River, Southwest China - Zhongxuan Liang; Keyi Wang; Hongming Cai; Zhongwei Wang; Wei Yuan; Jiubin Chen (Acta Geochimica, 2025)

Design of F doped sulfide bifunctional catalyst and investigation on the mechanism transformation of oxygen evolution reaction - Nianwen Song; Keyi Lv; Bo Feng; Ziyong Zhang; Xiangwen Tan; Yanfei Wei; Ziyang Yan; Yuchao Zhang; Xiaofei Yu; Lanlan Li; Xinghua Zhang; Xiaojing Yang; et al. (Chemical Engineering Journal, 2025)

Preparation, separation, and identification of antioxidant peptides from protein hydrolysate of Polygonatum cyrtonema Hua - Yanyan Zhang; Shengjun Ma; Haixia Li; Peizi Liu; Keyi Chen; Wei Cai (Food Bioscience, 2024)

Convenient synthesis of granulated Li/Al-layered double hydroxides/chitosan composite adsorbents for lithium extraction from simulated brine with a high Mg2+/Li+ ratio - Liqin Zhao; Xiaojie Zhang; Keyi Liu; Xin Liu; Yuefa Gong; Hong Peng; Wei Qi (Chemical Engineering Journal, 2024)

Identification and characterization of autoallododecaploid barnyard grass (Echinochloa crus-galli L.) induced by in vitro colchicine treatment - Keyi Liu; Xiaoling Zhou; Wei Wang; Xiaoxiao Wu; Ziwei Zhao; Xiaolu Yang; Ziyi Feng; Pincang Lv; Jie Wang; Wangwen Zhu; Xianhua Zhang; Yuchi He; et al. (In Vitro Cellular & Developmental Biology - Plant, 2024)

Water–Energy–Land Reallocation and Multiobjective Optimization in the Agricultural System - Jue Wang; Keyi Ju; Xiaozhuo Wei (Water Resources Management, 2024)

Attentional impairment and altered brain activity in healthcare workers after mild COVID-19 - Keyi Lin; Yaotian Gao; Wei Ji; Yan Li; Wei Wang; Mengcheng Du; Jia Liu; Zhengyu Hong; Tao Jiang; Yuyang Wang (Brain Imaging and Behavior, 2024)
Severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) is highly transmissible and pathogenic. Patients with mild cases account for the majority of those infected with coronavirus disease 2019 (COVID-19). Although there is evidence that many patients with COVID-19 have varying degrees of attentional impairment, little is known about how SARS-COV-2 affects attentional function. This study included a high-risk healthcare population divided into groups of healthcare workers (HCWs) with mild COVID-19 (patient group, n = 45) and matched healthy HCWs controls (HC group, n = 42), who completed general neuropsychological background tests and Attention Network Test (ANT), and underwent resting-state functional magnetic resonance imaging (rs-fMRI) using amplitude of low-frequency fluctuation (ALFF) to assess altered brain activity; Selective impairment occurred in orienting and executive control networks, but not in alert network, in the patient group, and widespread cognitive impairment encompassing general attention, memory, and executive dysfunction. Moreover, the patient group had significantly lower ALFF values in the left superior and left middle frontal gyri than the HC group. SARS-COV-2 infection may have led to reduced brain activity in the left superior and left middle frontal gyri, thus impairing attentional orienting and executive control networks, which may explain the development of attentional deficits after COVID-19.

Effects of four diets on the metabolism of megalopa metamorphosis of the mud crab, Scylla paramamosain - Keyi Ma; Zhiqiang Liu; Guangde Qiao; Lingbo Ma; Fengying Zhang; Ming Zhao; Chunyan Ma; Wei Wang (Frontiers in Marine Science, 2023)
Dietary intake is an essential source of energy and nutrients, and plays an irreplaceable role in the breeding of S. paramamosain seedlings. In this study, live Artemia nauplii (LA), compound feeds (CF), frozen copepods (FC) and frozen adult Artemia (FA) were utilized as feed during the megalopa stage. To determine the impact that diet has on the metabolism of crablets that underwent metamorphosis from the megalopa stage, analyses of both metabolomics and fatty acid content were conducted. In the LC-MS-based metabolomics analysis, a total of 104, 205 and 83 significantly different metabolites (SDMs) were identified after being fed with FC, FA, and CF, respectively, as compared to the LA group. Furthermore, significant differences in KEGG compounds among the three comparisons exhibited similarity and were mainly associated with categories such as “Lipids”, “Hormones and transmitters”, and “Peptides”. The fatty acid content analysis indicated that the ΣMUFA was significantly higher in the LA and CF groups compared to the other two groups. In contrast, the highest level of ΣPUFA was found in the LA group. In addition, the CF group showed significantly higher expression levels of the fatty acid synthesis genes, FAS and ACC . Conversely, the expression level of the fatty acid decomposition-related gene CPT1 was the highest in the LA group. In comparison with the FA group, the expression level of FABP3 was significantly decreased in the LA and CF groups. In summary, there were significant differences observed in the metabolic profiles of crablets that metamorphosed from the megalopa under different diets. Our experimental results suggested that LA is more advantageous in the cultivation of the S. paramamosain megalopa compared to the other three diets. While it remains a diet that cannot be entirely substituted at present, LA has the potential to improve the culture performance of the S. paramamosain megalopa. The current study could provide valuable data into the development of artificial diets necessary for the future of the mud crab seedling breeding industry.

Improving quantification of methane point source emissions from imaging spectroscopy - Zhipeng Pei; Ge Han; Huiqin Mao; Cuihong Chen; Tianqi Shi; Keyi Yang; Xin Ma; Wei Gong (Remote Sensing of Environment, 2023)

A comprehensive evaluation of the security of the water-energy-food systems in China - Keyi Ju; Jue Wang; Xiaozhuo Wei; Hao Li; Siyang Xu (Sustainable Production and Consumption, 2023)

Suppression of ETI by PTI priming to balance plant growth and defense through an MPK3/MPK6-WRKYs-PP2Cs module - Dacheng Wang; Lirong Wei; Ting Liu; Jinbiao Ma; Keyi Huang; Huimin Guo; Yufen Huang; Lei Zhang; Jing Zhao; Kenichi Tsuda; Yiming Wang (Molecular Plant, 2023)

Short-term effects of ambient particulate matter (PM1, PM2.5 and PM10) on influenza-like illness in Guangzhou, China - Jianyun Lu; Keyi Wu; Xiaowei Ma; Jing Wei; Zelin Yuan; Zhiwei Huang; Weidong Fan; Qi Zhong; Yining Huang; Xianbo Wu (International Journal of Hygiene and Environmental Health, 2023)

Astronomical Tide and Storm Surge Signals Observed in an Isolated Inland Maar Lake Near the Coast - Mingming Li; Chunyan Li; Lingling Xie; Wei Huang; Quanan Zheng; Keyi Tan; Yingbin Hong (Journal of Marine Science and Engineering, 2021)
Aimed at the explanation of clear tidal signal and storm surge signals in a closed inland lake near the coast (the Huguangyan Lake), this work uses a combined approach with observations and model experiments. Huguangyan Lake is a closed inland freshwater coneless volcanic crater lake near the coast in tropical southern China, less than 5 km from an estuary. It has a diameter of about 1.5 km and relatively deep water of up to 20 m. Bottom pressure was measured from an acoustic Doppler current profiler (ADCP) for 10 days in September 2018 and 10 days in January 2019. The observations encompass the period of Typhoon Mangkhut, which passed the region when it made its landfall. The time series demonstrate clear tidal and subtidal signals. The tidal signal remains even if we exclude the barometric pressure effect. Interestingly, the lake has no surface connection with the ocean. The astronomical tide has an amplitude of about 2 cm. The major tidal signals include the principal solar semidiurnal (S2) and lunisolar (K1) constituents. During the passage of Typhoon Mangkhut, the water level variability inside the lake increased by an order of magnitude (>0.3 m). To examine whether the lake water level change was due to the natural oscillations inside the lake (or seiche), a numerical wind-driven hydrodynamics model was designed using the 3-D Finite Volume Community Ocean Model (FVCOM). The results show that a small first-order seiche can be generated, but only with a time scale of minutes and with a magnitude much smaller than the observed surface elevation changes. This excludes any measurable seiche and the observed surface elevation change inside the lake cannot be wind-driven. Moreover, tides inside the lake are not generated by tidal potential, as the lake is too small for having a locally generated tide. The main result of our study has therefore excluded the local tidal-generating force, wind-driven seiche, and barometric effect, as possible causes of the lake oscillation which has tidal and subtidal signals. The subtidal variation is at least one order of magnitude greater than tides inside the lake and is caused by weather-induced overall coastal ocean water level oscillations transmitted into the lake through groundwater connection. All these lead to the major conclusion that the lake is connected to the coastal ocean through groundwater.

Toonamicrocarpavarin, a new tirucallane-type triterpenoid from Toona Ciliata - Ling Zhang; Jianjun Xia; Yanqing Duan; Keyi Wei; Rui Gao; Dasan Li; Xiaomin Liu; Tiandong Zhang; Minghua Qiu (Natural Product Research, 2021)

Discrimination of Tourette Syndrome Based on the Spatial Patterns of the Resting–State EEG Network - Keyi Duan; Qian Wu; Yuanyuan Liao; Yajing Si; Joyce Chelangat Bore; Fali Li; Qin Tao; Li Lin; Wei Lei; Xudong Hu; Dezhong Yao; Changfu Pei; et al. (Brain Topography, 2021)

Carboniferous integrative stratigraphy and timescale of China - Xiangdong Wang; Keyi Hu; Wenkun Qie; Qingyi Sheng; Bo Chen; Wei Lin; Le Yao; Qiulai Wang; Yuping Qi; Jitao Chen; Zhuoting Liao; Junjun Song (Science China Earth Sciences, 2019)

Cloning and functional characterization of PjCAO gene involved in chlorophyll b biosynthesis in Pseudosasa japonica cv. Akebonosuji - Keyi Jiang; Mingbing Zhou; Haiyun Yang; Wei Fang (Trees, 2016)

The Phosphoenolpyruvate Carboxykinase of Mycobacterium Tuberculosis Induces Strong Cell-Mediated Immune Responses in Mice - Keyi Liu; Xuelian Ba; Jinzhi Yu; Jin Li; Qingkuan Wei; Guangdong Han; Guiping Li; Yong Cui (Molecular and Cellular Biochemistry, 2006)